The Rise of the Covenant of Redemption in the Theology of Samuel Rutherford - Bostock, Sam (Early Modern History and Modern History E-Books Online, Collection 2025., 2025)
The Church of Scotland divine Samuel Rutherford (1600-61) was among the first theologians to say that Christ's saving work took place to fulfill an agreement between God and Christ that had been made in eternity. By placing Rutherford's major statements of this new doctrine in their various social, political, polemical, and pastoral contexts, this book provides a fresh explanation for the dramatic rise of the eternal covenant of redemption to become the cornerstone of Reformed federal theology and offers a case-study in the development of doctrine.